Taxonomy of the genus Ischnocolus in the Middle East, with description of a new species from Oman and Iran (Araneae: Theraphosidae) - Montemor, Vivian M. [UNESP]; West, Rick C.; Zamani, Alireza; Moradmand, Majid; Wirth, Volker V.; Wendt, Ingo; Huber, Siegfried; Guadanucci, Jose Paulo L. [UNESP] (Taylor & Francis Ltd, 2020)
Spider material collected from Oman and Iran revealed a new species of the genus Ischnocolus Ausserer, 1871, which is described as I. vanandelae sp. n. New records of I. jickelii L. Koch, 1875 from Saudi Arabia, Yemen and United Arab Emirates show a larger distribution of this species than previously known. The natural history of I. vanandelae sp. n. and I. jickelii is described and the rather unusual colour polymorphism of the latter is discussed. The genus now includes eight species, whose distribution is mapped.
Keywords: Taxonomy; spiders; Mygalomorphae; Oman; Saudi Arabia; United Arab Emirates